Evaluation of the Performance of Rainwater Harvesting Systems for Domestic Use in Tlalpan, Mexico City - Niall Patrick Nolan; Cecilia Lartigue (Salehan Institute of Higher Education, 2017)
Rainwater harvesting (RWH) as an alternative means of providing water in domestic contexts, is viewed as an effective supply option worldwide. In Mexico City, the water situation is critical and the provision of water services to the population represents a formidable challenge for the city’s water utilities. The main objective of this study is to evaluate the potential for RWH to supply domestic properties in Tlalpan, 1 of 16 delegations in the city with one of the highest percentages of homes unconnected to the distribution network. Results show RWH can meet 88% of household water demand during the 6 month wet season, with an annual saving of 55%. Modelling a World Health Organisation minimum demand of 20 l/p/d as a means of resilience management in the event of a water crisis, 6-month and annual savings were 99% and 80% respectively. The minimum tank size to achieve wet season savings of 90% was 6m3 in two precipitation bands and tank sizes of 13,000 – 17,000L were sufficient in 3 out of 4 to prevent overspill. The report concludes RWH is a viable method of providing water in the south of the city and should be part of an integrated water management solution.